Emerging therapies for small cell lung cancer - Yang, Sen; Zhang, Zhe; Wang, Qiming (Journal of hematology and oncology, 2019)
Currently, chemotherapy remains the standard treatment for first- and second-line management of small cell lung cancer (SCLC). Immunotherapy has made progress in the treatment of SCLC, and nivolumab, pembrolizumab, atezolizumab, and durvalumab have led to significant improvements in clinical outcomes of SCLC. Regarding options in other classes of therapy, the cytotoxic drug lurbinectedin was granted orphan drug status based on a remarkable objective response rate of 39.3%. In addition, an increase in progression-free survival (PFS) was achieved in a phase II study of anlotinib (ALTER 1202). Future prospects for even better outcomes in SCLC lie in novel ways to integrate immunotherapy and small-molecule TKI drugs. Innovative clinical trial designs are needed to efficiently explore the increasing number of options with new drugs and new combinations thereof for SCLC.